(untitled) (Comparative & International Education Series, 2021)
This chapter will explore these realities by taking a case-study approach looking at two partner institutions, one in the UK and one in Thailand, and considering their internationalization programs, similarities and differences between them and their subsequent impact. We investigate to what extent arrangements such as these are ethical, and we will conclude our chapter with a summary of the implications and pitfalls of such programs, with particular focus on the responsibilities of Western universities to contribute to having meaningful, equal collaborations to support the internationalization of higher education.